Clinicopathological Profile of Cervical Tuberculous Lymphadenitis: Experience from Universitas Airlangga Hospital - Ari Wanda, Dewi Sartika; rahaju, anny setijo; Sita Sari, Aditya (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Tuberculous lymphadenitis is the most common form of extrapulmonary TB, and the most common location is in the neck. It is quite challenging to diagnose lymph TB. Clinical presentation, along with multiple modalities is usually used to diagnose it. This retrospective observational descriptive study collected data from medical recordsof Universitas Airlangga hospital of 147 patients suffering from tuberculous lymphadenitis during the period of 2022-2023. All patients in this study presented with lumps in the neck area (painless nodules [n = 90, 61.22%] and unilateral nodules [n = 133, 90.48%]), while other symptoms such as fever, cough, and weight loss were less common. FNAB revealed 60 patients (40.8%) confirmed with tuberculous lymphadenitis primary tuberculous lymphadenitis (n = 48, 32.6%) and tuberculous lymphadenitis with secondary infections (n = 12, 8.2%). The histopathological review mostly revealed tuberculous lymphadenitis (88%). Only 10 patients (34.48%) with tuberculous lymphadenitis were found from neck ultrasound examination. Eighty-five patients performed GeneXpert MTB/RIF assay and showed positive results in most cases (n = 43, 50.59%). Negative acid-fast bacilli (AFB) results in granulomatous lesions, do not exclude the possibility of tuberculosis. The combination of pathology examination, GeneXpert MTB/RIF assay, and neck ultrasonography makes the diagnosis of cervical tuberculous lymphadenitis accurate.